Freeports, elites, and loopholes: A socio-spatial exploration of the globalized geographies of contemporary art trade using the TPSN-heuristic - Krell, Michael; Meyer, Frank (ERDKUNDE, 2024)
The globalized trade in artworks has undergone significant changes since the end of the Cold War: While its former Western centres, such as New York and London, continue to dominate the discourse on high price segments with well-attended art fairs and influential auction houses, new actors challenge these former major players, new customers push into the market, and inflationary price increases have been recorded in recent years. From the perspective of systematic geographical research, however, this field of economically globalized trade has been largely neglected so far. With the help of a systematic literature analysis, this article examines the existing knowledge on the globalized art market across disciplines and systematises it with the help of the so-called TPSN model along the spatial categories of territory, place, scale, and network. Based on this analysis, we developed five core findings of the globalized art market that can serve as a foundation for future geographical research projects.